2011
DOI: 10.1517/13543776.2011.594040
|View full text |Cite
|
Sign up to set email alerts
|

Semicarbazide-sensitive amine oxidase/vascular adhesion protein-1: a patent survey

Abstract: SSAO/VAP-1 is a promising anti-inflammatory target. Another important field for therapeutic application of these inhibitors may be ophthalmology, due to their antiangiogenic effects. SSAO substrates might also be of therapeutic value in the treatment of diabetes; however, more extensive research has to be undertaken to validate this approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 116 publications
0
29
0
Order By: Relevance
“…The common element in those 3 reports was that neuroprotection could be achieved through treatment with highly selective blockers of vascular adhesion protein-1 (VAP-1). That endothelial protein is thought to play a key role in promoting adhesion and transmigration of polymorphonuclear leukocytes, monocytes, and lymphocytes (e.g., Dunkel et al, 2011;Hernandez-Guillamon et al, 2010;Watcharotayangul et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The common element in those 3 reports was that neuroprotection could be achieved through treatment with highly selective blockers of vascular adhesion protein-1 (VAP-1). That endothelial protein is thought to play a key role in promoting adhesion and transmigration of polymorphonuclear leukocytes, monocytes, and lymphocytes (e.g., Dunkel et al, 2011;Hernandez-Guillamon et al, 2010;Watcharotayangul et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The association of SSAO activity in plasma and in tissues for future vascular outcomes merits further research, as SSAO has been suggested as a therapeutic target, particularly in relationship to its inflammatory and anti-angiogenic effects. 47 …”
Section: Discussionmentioning
confidence: 99%
“…A link between elevated plasma SSAO and mortality in CHF patients suggests that SSAO inhibition could prevent additional vascular damage [119]. A patent review of SSAO inhibitors was published in 2011 [120]. Several companies, led by Proximagen, have disclosed small molecules recently.…”
Section: Natriuretic Peptidesmentioning
confidence: 99%